2008
DOI: 10.1101/gad.1641808
|View full text |Cite
|
Sign up to set email alerts
|

Fgf-dependent depletion of microRNA-133 promotes appendage regeneration in zebrafish

Abstract: Appendage regeneration is defined by rapid changes in gene expression that achieve dramatic developmental effects, suggesting involvement of microRNAs (miRNAs). Here, we find dynamic regulation of many miRNAs during zebrafish fin regeneration. In particular, miR-133 levels are high in uninjured fins but low during regeneration. When regeneration was blocked by Fibroblast growth factor (Fgf) receptor inhibition, high miR-133 levels were quickly restored. Experimentally increasing amounts of miR-133 attenuated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 25 publications
8
158
0
1
Order By: Relevance
“…The effect was pronounced at 6 days postamputation (dpa), after which the fins began to regenerate over time (data not shown), which is consistent with the half-life of the morpholinos but also indicates that the injections did not irreversibly block regeneration. These results demonstrate that an intact miRNA pathway is essential for regeneration and are consistent with the hypothesis that induction of specific miRNAs is needed for proper regeneration (19).…”
Section: Figsupporting
confidence: 76%
See 2 more Smart Citations
“…The effect was pronounced at 6 days postamputation (dpa), after which the fins began to regenerate over time (data not shown), which is consistent with the half-life of the morpholinos but also indicates that the injections did not irreversibly block regeneration. These results demonstrate that an intact miRNA pathway is essential for regeneration and are consistent with the hypothesis that induction of specific miRNAs is needed for proper regeneration (19).…”
Section: Figsupporting
confidence: 76%
“…miRNAs are a recently discovered class of genes that regulate gene expression at the posttranscriptional level and are required for development, stem cell maintenance, and renewal (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Recently, Yin et al (19) showed that fibroblast growth factor (Fgf) signaling alters the expression of multiple miRNAs during regeneration. One of the miRNA targets of Fgf signaling, miR-133, targets mps1, which encodes a kinase that regulates blastemal proliferation.…”
Section: Lef1 ͉ Mir-203mentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, the caudal fin regenerates by means of an epimorphic process similar to that of amphibian limbs, including the formation of a blastema (Poss et al, 2003), and involving many of the same signaling molecules, including Fgf20 (Whitehead et al, 2005;Stoick-Cooper et al, 2007a). In a recent study, Yin et al (2008) describe several miRNAs that are differentially expressed between normal and Fgf inhibited zebrafish tails. One of these, miR-133, is dramatically down-regulated during caudal fin regeneration, but high in normal tails.…”
Section: Micrornasmentioning
confidence: 99%
“…Genes and cell-signaling pathways that are involved in zebrafish fin regeneration have been previously characterized (Laforest et al, 1998;Tawk et al, 2000;Quint et al, 2002;Padhi et al, 2004;Smith et al, 2006;Jazwinska et al, 2007;Stoick-Cooper et al, 2007a, b;Wills et al, 2008;Yin et al, 2008;Chablais and Jazwinska, 2010). For example, Whitehead et al (2005) reported that the expression of fgf20a, a gene that encodes a member of the fibroblast growth factor family, plays important roles in the initiation of fin regeneration, and that decreases in fgf20a expression result in inhibition of fin regeneration.…”
Section: Introductionmentioning
confidence: 99%